Efisiensi Penurunan Kadar Kalsium Pada Air Laut Dengan Metoda Penukar Ion Yang Memanfaatkan Tanah - Roselyn Indah Kurniati; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Source of water in Bengkalis is difficult. Sea water can be a source of water in there. Once of alternative can be process sea water be clean water use ion exchange with clay. This experiment use coloumn with diameter 2 inchi and high 1,2 meter. Media who used is clay. Ratention time and particle measure used variation of this experiment. Rate of retention time are 60, 120, 180 minute and particle measure are -3+5, -5+10, -10+15 mesh. Concentration Ca before process is 128 mg/l and after process is 58,4-8,8 mg/l of variation. Over all, clay can be cause of concentration Ca. Finally, retention time and particle measure give to effect to cause metal in seawater with efisiensi Ca are 54,38-93,12%, with a CEC of clay is 122,93 meq / 100g.Keywords : Seawater, Ion Exchange, Clay, Ratention Time, Particle Measure